Peran Motivasi dan Kreativitas dalam Meningkatkan Minat Berwirausaha pada Generasi Muda - Bintang Maha Putra; Wulan Safitri; Fatma Tresno Ingtyas; Laurena Ginting (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to examine the role of motivation and creativity in increasing entrepreneurial interest among young people, particularly students of the Culinary Education Study Program at Universitas Negeri Medan. A qualitative approach was employed, with data collected through in-depth interviews involving 15 participants, consisting of students who have already started a business, those who have just begun, and those who are still hesitant to engage in entrepreneurship. The data were analyzed using the SWOT (Strengths, Weaknesses, Opportunities, Threats) framework to identify internal and external factors influencing entrepreneurial interest. The results indicate that motivation serves as the main driving factor in building persistence and enthusiasm to face business challenges, while creativity plays a key role in generating ideas and innovations that enhance competitiveness. These two factors have a synergistic relationship, mutually reinforcing each other in encouraging young people to start and develop sustainable businesses. The findings also highlight the importance of practice-based entrepreneurship education and social support in shaping young entrepreneurs who are independent, innovative, and adaptive to market changes.